Henry James and the new woman: a feminist reading of the Bostonians - Abbasi, Pyeaam (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
The Bostonians (1886) is known as Henry James’s lesbian novel in which the writer’s ambivalent look towards the New Woman can be explored. James was a subject/product of the complex discursive web of his time when such ideologies of the superiority of men over women were strictly observed. In that time the idea of same-sex bond was regarded as a threat to the traditional concept of heterosexual bonding. This study is an attempt to conclude James as the contributor to the notion of the New Woman since locating the issue in his novel is enough to make readers put many long-held conventions in question. In this study three important misspeaks are referred to: firstly, James shows the uniqueness of the relation between the two women of the novel; secondly, the writer shows Verena (Basil’s wife) changed into property; and finally James shows America’s potential for such big changes in attitude regarding women. Although James cannot remain untouched by certain ideologies of his time, he makes his readers think about a different possibility and future for both America and her modern woman.